Vestibular and balance function in veterans with chronic dizziness associated with mild traumatic brain injury and blast exposure - Akin, Faith W.; Murnane, Owen D.; Hall, Courtney D.; Riska, Kristal M.; Sears, Jennifer (Frontiers in Neurology, 2022)
The purpose of this study was to examine vestibular and balance function in individuals with chronic dizziness associated with mTBI/blast. A prospective case-control study design was used to examine ocular motor, vestibular function, and postural stability in veterans with symptoms of dizziness and/or imbalance following an mTBI or blast exposure (n = 77) and a healthy control group (n = 32). Significant group differences were observed for saccadic accuracy, VOR gain during slow harmonic acceleration at 0.01 Hz, cervical vestibular evoked myogenic potentials asymmetry ratio, composite equilibrium score on the sensory organization test, total Dynamic Gait Index score, and gait. The frequency of test abnormalities in participants with mTBI/blast ranged from 0 to 70% across vestibular, ocular motor, and balance/gait testing, with the most frequent abnormalities occurring on tests of balance and gait function. Seventy-two percent of the mTBI/blast participants had abnormal findings on one or more of the balance and gait tests. Vestibular test abnormalities occurred in 34% of the individuals with chronic dizziness and mTBI/blast, and abnormalities occurred more frequently for measures of otolith organ function (25% for cVEMP and 18% for oVEMP) than for measures of hSCC function (8% for SHA and 6% for caloric test). Abnormal ocular motor function occurred in 18% of the mTBI/blast group. These findings support the need for comprehensive vestibular and balance assessment in individuals with dizziness following mTBI/blast-related injury.